The prevalence of diabetes mellitus and relationship with socioeconomic status in the Indonesian population - Deri Indrahadi; Amika Wardana; Adi Cilik Pierewan (Jurnal Gizi Klinik Indonesia, 2021)
Background: The prevalence of diabetes mellitus is increasing globally and remains debated. Objective: This study examines the association of socioeconomic status with the prevalence of diabetes mellitus in Indonesia. Methods: This study used a cross-sectional design. Data obtained from the 2014 Indonesia Family Life Survey (IFLS), a nationally representative population survey data, which polled 30,497 individuals age 16 years and over in 13 provinces in Indonesia. Logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CI) for the prevalence of diabetes mellitus with socioeconomic status. Results: Education level, employment status, age, and hypertension are related to the prevalence of diabetes mellitus. According to educational level, individuals with lower education level were more likely to have diabetes mellitus than those who had a higher level of education (OR=1.42; 95% CI: 1.21-1.67), higher risk was also found in those who were unemployed (OR=1.55; 95% CI: 1.33-1.82). Besides, age and hypertension were independent factors for a higher prevalence of diabetes mellitus, age >55 (OR=4.71; 95% CI: 4.06-5.46), hypertension (OR=5.86; 95% CI: 5.00-6.87). Diabetes mellitus also show significantly higher among individuals living in urban areas compared to individuals living in rural areas (OR=2.13; 95% CI: 1.78-2.55). Conclusions: Socioeconomic status has a significant association with the prevalence of diabetes mellitus among people above 15 years old in Indonesia. The government needs to design a preventive program to control this disease by considering the risk factors that may lead to the development of diabetes mellitus in Indonesia.